The Legality of the Living Law in the New Indonesian Penal Code - Ferry Fathurokhman; Anna Erliyana; Ali Masyhar; Mutiara Dwi Sari; Iren Sudarya (Universitas Negeri Semarang, 2026)
Since the Netherland introduced a Penal Code, The Indonesian people are required to rely on the principle of legality as the primary source of law in determining criminal offences. The old penal code does not allow living law to function as an independent source of law. On January 2nd, 2023, the new Indonesian Penal Code was finally established, which will enter into force within three years after its issuance. The provision of living law in the new Indonesian penal code is formulated in article 2. In its first verse, it is written that “provisions, as referred to Article 1 (legality principle), does not negate the validity of the law that live in a society which stipulates that someone deserves to be punished even though the act is not regulated in this Law.